Prevalence of Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus Carriage in Three Populations - Kottler, S; Middleton, J.R; Perry, J; Weese, J.S; Cohn, L.A (Journal of veterinary internal medicine, 2010)
Background: A higher prevalence of methicillin‐resistant Staphylococcus aureus (MRSA) colonization is reported in healthcare workers compared with nonhealthcare workers. Hypothesis: The prevalence of MRSA colonization differed in people and pets in households with healthcare workers as compared with households without healthcare workers. Subjects: A person and 1 dog or cat from 586 households defined as either a nonhealthcare (n = 213), veterinary healthcare (n = 211), or human healthcare (n = 162) worker household. Methods: Prospective cross‐sectional study. Samples from humans and pets were cultured in vitro. Staphylococcus aureus was identified as methicillin sensitive (MSSA) or MRSA with mecA polymerase chain reaction. Pulsed‐field gel electrophoresis and spa‐typing were used to characterize relatedness of S. aureus and MRSA and assign USA types. Results: The prevalence of MSSA and MRSA in humans was 21.5% (126/586) and 5.63% (33/586), respectively, and 7.85% (46/586) and 3.41% (20/586), respectively, in pets. There were no differences in prevalences of either MSSA or MRSA between household types. The proportion of MRSA among all S. aureus isolates in humans and pets was 20.8% (33/159) and 30.3% (20/66), respectively. In <1.0% (4/586) of households, the same strain of MRSA was found in both a person and a pet. Conclusions and Clinical Importance: There were no differences in the prevalences of MSSA or MRSA between healthcare worker and nonhealthcare worker households. Pets and people colonized with S. aureus were as likely to be colonized with MRSA. Colonization of a person and their pet with the same strain of MRSA was rare.